Negative ions in liquid helium - Khrapak, A.G.; Schmidt, W.F. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2011)
Structure of negative ions in liquid 4He is analyzed. The possibility of cluster or bubble formation around impurity ions of both signs is discussed. It is demonstrated that in superfluid helium, around negative alkalineearth metal ions, bubbles are formed and, around halogen ions, clusters are formed. The nature of “fast” and “exotic” negative ions is also discussed. It is assumed that the “fast” ions are negative ions of helium excimer molecules localized inside bubbles. The “exotic” ions are stable negative impurity ions, which are always present in small amounts in gas discharge plasma. Around such ions, bubbles or clusters are created with radius smaller the radius of electron bubbles.